A qualitative and quantitative comparison between Web scraping and API methods for Twitter credibility analysis - Dongo I. (2021)
This research was supported by the FONDO NACIONAL DE DESARROLLO CIENTÍFICO, TECNOLÓGICO Y DE INNOVACIÓN TECNOLÓGICA – FONDECYT as executing entity of CONCYTEC under grant agreement no. 01–2019-FONDECYT-BM-INC.INV in the project RUTAS: Robots para centros Urbanos Turísticos Autónomos y basados en Semántica.